Evaluation of individual low‐dose dexamethasone suppression test patterns in naturally occurring hyperadrenocorticism in dogs. (2nd March 2018) - Bennaim, Michael; Shiel, Robert E.; Forde, Christopher; Mooney, Carmel T.
Abstract : Background: Dogs with hyperadrenocorticism (HAC) may be more mildly affected at the time of diagnosis today, which could influence the prevalence of associated clinical and clinicopathological abnormalities and diagnostic test performance. Different low‐dose dexamethasone suppression test (LDDST) result patterns have not been evaluated individually. Objectives: To assess the current features of HAC and evaluate if the diagnostic test performance of individual LDDST result patterns differ. Animals: One hundred and twenty‐three dogs undergoing investigation for HAC. Methods: Retrospective evaluation of dogs in which a LDDST was performed and HAC confirmed or excluded by alternative means. Cases with basal cortisol concentrations ( t 0 ) < 1 μg/dL were excluded. Each LDDST result was classified as (a) complete suppression ( t 3 and t 8 < 1 μg/dL), (b) lack of suppression ( t 3 and t 8 > 1 μg/dL and both > 50% t 0 ), (c) partial suppression ( t 3 and t 8 > 1 μg/dL but either < 50% t 0 ), (d) escape ( t 8 > 1 μg/dL and t 3 < 1 μg/dL) or ( e ) inverse ( t 3 > 1 μg/dL and t 8 < 1 μg/dL) pattern. Results: Fifty‐nine (48%) dogs were diagnosed with HAC and 64 (52%) with non‐adrenal illness. Hyperadrenocorticism cases had similar clinicopathological abnormalities compared to previous reports. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) (95% confidence interval [CI]) of the LDDST for diagnosing HAC were 96.6 (91.9‐100)%, 67.2 (55.7‐78.7)%, 73.1 (63.2‐82.9)%, and 95.6 (89.5‐100)%, respectively. Lack of suppression pattern had the highest PPV (93.9 [85.8‐100]%) followed by the partial suppression pattern (67.9 [50.6–85.2]%) and escape or inverse pattern (36.8 [15.1–58.5]%). Conclusions and Clinical Importance: A lack of suppression LDDST pattern has the highest PPV for diagnosing HAC followed by a partial suppression pattern. By contrast, the escape or inverse pattern provided limited support of HAC.